2000
DOI: 10.1103/physreva.62.022708
|View full text |Cite
|
Sign up to set email alerts
|

Dielectronic recombination of lithiumlikeNi25+ions: High-resolution rate coefficients and influence of external crossed electric and magnetic fields

Abstract: Absolute dielectronic recombination (DR) rates for lithiumlike Ni 25+ (1s 2 2s) ions were measured at high-energy resolution at the Heidelberg heavy-ion storage ring TSR. We studied the center-of-mass energy range 0-130 eV which covers all ∆n=0 core excitations. The influence of external crossed electric (0-300 V/cm) and magnetic (41.8-80.1 mT) fields was investigated. For the measurement at near-zero electric field resonance energies and strengths are given for Rydberg levels up to n=32; also Maxwellian plasm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Various aspects of recombination measurements at the heavy-ion storage ring TSR of the Max-Planck-Institut für Kernphysik (MPI-K) in Heidelberg, Germany, have been described by Kilgus et al (1992), Lampert et al (1996), Pastuszka et al (1996), Müller & Wolf (1997), and Schippers et al (2000Schippers et al ( , 2001. For the present experiment a Mg  ion beam with an energy of about 4.2 MeV/u was provided by the MPI-K linear accelerator facility and injected into the storage ring.…”
Section: Methodsmentioning
confidence: 99%
“…Various aspects of recombination measurements at the heavy-ion storage ring TSR of the Max-Planck-Institut für Kernphysik (MPI-K) in Heidelberg, Germany, have been described by Kilgus et al (1992), Lampert et al (1996), Pastuszka et al (1996), Müller & Wolf (1997), and Schippers et al (2000Schippers et al ( , 2001. For the present experiment a Mg  ion beam with an energy of about 4.2 MeV/u was provided by the MPI-K linear accelerator facility and injected into the storage ring.…”
Section: Methodsmentioning
confidence: 99%
“…dominate the dielectronic recombination process can be Starkmixed by weak electric fields (Burgess & Summers 1969), in particular the plasma microfield (Jacobs et al 1976), and so increase the partial rate coefficients by factors of 2, or 3, or more, over a wide range of n. Recently, the picture has been further complicated by the discovery that magnetic fields, when crossed with an electric field, strongly affect the electric field enhancement -by reducing it in most cases(see Robicheaux et al 1997;Bartsch et al 1999;Schippers et al 2000;Böhm et al 2001). While this suppression of the electric field enhancement is advantageous towards the use of field-free dielectronic recombination data, it is disadvantageous in terms of trying to compute field-dependent data for plasma modelling.…”
Section: Experimental Validation Of Dielectronic Recombination Data Amentioning
confidence: 99%
“…The effects of external electric fields on dielectronic recombination are found to be quite significant by Griffin et al (1986) in their studies of Na-like ions P 4+ , S 5+ , Cl 6+ and by Griffin & Pindzola (1987) in their studies of Fe 15+ . Recent experimental (Bartsch et al 1997(Bartsch et al , 1999Böhm et al 2001Böhm et al , 2002Schippers et al 2000;Gwinner et al 2000), and theoretical studies (Robicheaux & Pindzola 1997;Robicheaux et al 1998;Griffin et al 1998;Mitnik et al 1999) have shown the importance of the effects of crossed external electric and magnetic fields. We expect that low charge Na-like ions will be more sensitive to the external fields, as is the case for Li-like ions (Badnell et al 1993).…”
Section: Introductionmentioning
confidence: 99%